TEACHER’S ROLE AND CHALLENGES IN TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) - Aziza Erkin qizi, Erkinova (PT. Antis International Publisher, 2025)
Objective: This study aims to examine the multifaceted role of teachers in English for Specific Purposes (ESP) instruction and the challenges they face in delivering discipline-specific language education. Method: Employing a qualitative research design, data were collected through surveys, interviews, and classroom observations involving twenty experienced ESP instructors from various academic disciplines, including business, engineering, and medicine. Results: The findings reveal that ESP teachers are expected to go beyond traditional language instruction by integrating content knowledge relevant to specific professional fields. Major challenges identified include limited subject-matter expertise, lack of ready-to-use instructional materials, and varying student language proficiencies. Strategies such as collaboration with subject experts, differentiated instruction, and learner-centered materials development were noted as effective in addressing these issues. Novelty: This study contributes to the growing body of ESP literature by highlighting the dual pedagogical demands placed on instructors and proposing practice-based recommendations to bridge the gap between language teaching and subject content mastery, particularly in under-researched multilingual contexts.